Hidden Attractors: New Horizons in Exploring Dynamical Systems - Jamal-Odysseas, Maaita (Journal of Applied Nonlinear Dynamics, 2026)
Nonlinear systems can be studied by their equivalent linearized systems in the region of equilibrium points. This fact led the study of dynamical systems to be focused near these points. On the contrary Hidden attractors can be found in systems with no equilibrium points, with one stable equilibrium or in systems with lines of equilibrium points. This forces us to ``sail in uncharted waters'' and opens new perspectives in the study of dynamical systems.